OPTIMALISASI PERAN KADER KESEHATAN DALAM MENINGKATKAN MANAJEMEN DIABETES SEBAGAI UPAYA PELAYANAN TERINTEGRASI PROGRAM PROLANIS - Ni Wayan Trisnadewi; Theresia Anita Pramesti; Sri Idayani; Ni Kadek Yuni Lestari (Bajang Institute, 2025)
This community service focuses on optimizing and educating health cadres in diabetes management through the prolanis program as an effort to control diabetes in type 2 DM patients. Cadre education is carried out as an approach to the community who can become the closest service providers for patients and families in implementing diabetes management. Diabetes management includes four pillars, namely diet, medication, physical exercise and education. As individuals with chronic illnesses, patients will feel bored with long-term treatment programs. In an effort to avoid treatment stress, patients need to receive support from the closest environment such as family and health service workers. Health cadres are health service workers who often come into contact with patients. Cadres have a very important role in efforts to organize activities in community health center services. This program aims to provide knowledge to health cadres and the community in line with Prolanis activities regarding the importance of health knowledge in diabetes management so that they will be able to become knowledge agents for DM patients